system3d := a[1](a[1])+a[2]*a[4]+a[3]*a[7]-a[1](a[1])-a[2]*a[10]-a[3]*a[19], a[1]*a[2]-a[1]*a[2]+a[2]*a[5]-a[2]*a[11]+a[3]*a[8]-a[3]*a[20], a[1]*a[3]-a[1]*a[3]+a[2]*a[6]-a[2]*a[12]+a[3]*a[9]-a[3]*a[21], a[1]*a[4]-a[1]*a[4]-a[2]*a[13]-a[3]*a[22]+a[4]*a[5]+a[6]*a[7], a[2]*a[4]+a[5](a[5])+a[6]*a[8]-a[1]*a[5]-a[2]*a[14]-a[3]*a[23], a[3]*a[4]+a[5]*a[6]+a[6]*a[9]-a[1]*a[6]-a[2]*a[15]-a[3]*a[24], a[1]*a[7]+a[4]*a[8]+a[7]*a[9] = a[1]*a[7]+a[2]*a[16]+a[3]*a[25], a[2]*a[7]+a[5]*a[8]+a[8]*a[9] = a[1]*a[8]+a[2]*a[17]+a[3]*a[26], a[3]*a[7]+a[6]*a[8]+a[9](a[9]) = a[1]*a[9]+a[2]*a[18]+a[3]*a[27];

print(`output redirected...`); # input placeholder

a[2] a[4] - a[2] a[10] + a[3] a[7] - a[3] a[19],

a[2] a[5] - a[2] a[11] + a[3] a[8] - a[3] a[20],

a[2] a[6] - a[2] a[12] + a[3] a[9] - a[3] a[21],

-a[2] a[13] - a[3] a[22] + a[4] a[5] + a[6] a[7], a[2] a[4]

+ a[5](a[5]) + a[6] a[8] - a[1] a[5] - a[2] a[14] - a[3] a[23],

-a[1] a[6] - a[2] a[15] + a[3] a[4] - a[3] a[24] + a[5] a[6]

+ a[6] a[9], a[1] a[7] + a[4] a[8] + a[7] a[9] = a[1] a[7]

+ a[2] a[16] + a[3] a[25], a[2] a[7] + a[5] a[8] + a[8] a[9] =

a[1] a[8] + a[2] a[17] + a[3] a[26], a[3] a[7] + a[6] a[8]

+ a[9](a[9]) = a[1] a[9] + a[2] a[18] + a[3] a[27]

solve({system3d}, {a[1]*a[2], a[1]*a[3], a[1]*a[4], a[1]*a[5], a[1]*a[6], a[1]*a[7], a[1]*a[8], a[1]*a[9], a[2]*a[4], a[2]*a[5], a[2]*a[6], a[2]*a[7], a[2]*a[10], a[2]*a[11], a[2]*a[12], a[2]*a[13], a[2]*a[14], a[2]*a[15], a[2]*a[16], a[2]*a[17], a[2]*a[18], a[3]*a[4], a[3]*a[7], a[3]*a[8], a[3]*a[9], a[3]*a[19], a[3]*a[20], a[3]*a[21], a[3]*a[22], a[3]*a[23], a[3]*a[24], a[3]*a[25], a[3]*a[26], a[3]*a[27], a[4]*a[5], a[4]*a[8], a[5]*a[6], a[5]*a[8], a[6]*a[7], a[6]*a[8], a[6]*a[9], a[7]*a[9], a[8]*a[9], a[1](a[1]), a[5](a[5]), a[9](a[9])});

%;

**Warning, solving for expressions other than names or functions is not recommended.**

{a[1] a[2] = a[1] a[2], a[1] a[3] = a[1] a[3],

a[1] a[4] = a[1] a[4], a[1] a[5] = a[2] a[10] - a[3] a[7]

+ a[3] a[19] + a[5](a[5]) + a[6] a[8] - a[2] a[14]

- a[3] a[23], a[1] a[6] = -a[2] a[15] + a[3] a[4] - a[3] a[24]

+ a[5] a[6] + a[6] a[9], a[1] a[7] = a[1] a[7], a[1] a[8] = a[

2] a[7] - a[2] a[17] - a[3] a[26] + a[5] a[8] + a[8] a[9], a[1]

a[9] = a[3] a[7] + a[6] a[8] + a[9](a[9]) - a[2] a[18]

- a[3] a[27], a[2] a[4] = a[2] a[10] - a[3] a[7] + a[3] a[19],

a[2] a[5] = a[2] a[11] - a[3] a[8] + a[3] a[20],

a[2] a[6] = a[2] a[12] - a[3] a[9] + a[3] a[21],

a[2] a[7] = a[2] a[7], a[2] a[10] = a[2] a[10],

a[2] a[11] = a[2] a[11], a[2] a[12] = a[2] a[12],

a[2] a[13] = -a[3] a[22] + a[4] a[5] + a[6] a[7],

a[2] a[14] = a[2] a[14], a[2] a[15] = a[2] a[15],

a[2] a[16] = -a[3] a[25] + a[4] a[8] + a[7] a[9],

a[2] a[17] = a[2] a[17], a[2] a[18] = a[2] a[18],

a[3] a[4] = a[3] a[4], a[3] a[7] = a[3] a[7],

a[3] a[8] = a[3] a[8], a[3] a[9] = a[3] a[9],

a[3] a[19] = a[3] a[19], a[3] a[20] = a[3] a[20],

a[3] a[21] = a[3] a[21], a[3] a[22] = a[3] a[22],

a[3] a[23] = a[3] a[23], a[3] a[24] = a[3] a[24],

a[3] a[25] = a[3] a[25], a[3] a[26] = a[3] a[26],

a[3] a[27] = a[3] a[27], a[4] a[5] = a[4] a[5],

a[4] a[8] = a[4] a[8], a[5] a[6] = a[5] a[6],

a[5] a[8] = a[5] a[8], a[6] a[7] = a[6] a[7],

a[6] a[8] = a[6] a[8], a[6] a[9] = a[6] a[9],

a[7] a[9] = a[7] a[9], a[8] a[9] = a[8] a[9],

a[1](a[1]) = a[1](a[1]), a[5](a[5]) = a[5](a[5]),

a[9](a[9]) = a[9](a[9])}

the program runs however the warning message pops ...what can i do to eliminate the problem???